Implementing an English Day Program to Support Students’ Public Speaking: A Qualitative Case Study at an Indonesian Junior High School - Safitri Pangesti Dewi; Tina Priyantin; Poppy Sofia Hidayati (Asshika: Journal of English Language Teaching and Learning, 2024)
In Indonesian schools, particularly in Bogor, the English Day program mandates weekly English use to enhance speaking skills. This qualitative case study examines how the program is implemented to support public speaking at Ibnu Hajar Islamic Junior High School. Participants included eighth- and ninth-grade students (n=4 for interviews), selected for their active engagement during observations. Data were collected via classroom observations (four weeks, eight sessions) and semi-structured interviews. Thematic analysis revealed two primary activities presentations and storytelling that foster public speaking. Students prepared materials, practiced nonverbal cues (e.g., body language, intonation), and delivered structured talks (opening, body, closing). Although occasional code-mixing with Bahasa Indonesia occurred, teachers reinforced English use through vocabulary drills as mild reinforcement, leading to improvements in pronunciation, vocabulary, and confidence. The program creates a supportive environment for real-world English application, though limitations included unobserved activities like debates. Findings underscore the program's role in building communicative competence.